Refusing to TAP out: 16 new human TEIPPs identified - Gigoux, Mathieu; Wolchok, Jedd (The Journal of experimental medicine, 2018)
In this issue of , Marijt et al. (https://doi.org/10.1084/jem.20180577) report their discovery of 16 novel human TAP-independent TEIPP peptides, whereas only one had been previously identified. This opens the door to new therapeutic options for patients with TAP-deficient tumors.